The Effect of Giving Dates (Phoenix dactylifera) on Hemoglobin Levels in Anemic Adolescent Girls at Prima Nusantara Vocational School, Bukittinggi, Indonesia - Nova H, Desri; Yeltra Armi; Mutia Felina (HM Publisher, 2024)
Anemia in adolescent girls is a health problem that often occurs in Indonesia. Dates (Phoenix dactylifera) is a fruit that is rich in iron and folate, which play an important role in the formation of hemoglobin. This study aims to determine the effect of giving dates on hemoglobin levels in anemic adolescent girls at Prima Nusantara Vocational School, Bukittinggi Indonesia. This research used a quasi-experimental design with a pretest-posttest with the control group design. A total of 30 adolescent girls who experienced anemia were randomly divided into two groups, namely the intervention group which was given 3 dates per day for 4 weeks and the control group which was given no dates. Hemoglobin levels were measured before and after the intervention. The results showed that there was a significant increase in hemoglobin levels in the intervention group compared to the control group (p < 0.05). Giving dates can increase hemoglobin levels in adolescent girls who suffer from anemia.